Uji Daya Hambat Rebusan Daun Kitolod (Hippobroma longiflora) Terhadap Pertumbuhan Staphylococcus aureus - Puji Hastuti, Handayani; Prian Nirwana, Ardy (Jurnal Farmasi (Journal of Pharmacy), 2021)
Conjunctivitis is inflammation of the conjunctiva. One of the bacteria that causes conjunctivitis most often is Staphylococcus aureus. Hippobroma longiflora is widely used by traditional people to treat eye disorders such as conjunctivitis because it has antimicrobial substances such as flavonoids, saponins, and alkaloids. This study aims to determine the radical zones that can be formed from the decoction of H. longiflora leaves against the growth of S.aureus. This research method is descriptive experimental. The sampling technique used was quota sampling. This study used a negative control with sterile distilled water and a positive control for 30 µg chloramphenicol. The decoction of H. longiflora leaves can inhibit the growth of S. aureus as indicated by the results obtained that form a radical zone of each concentration variation of 20%, 40%, 60%, 80%, and 100% respectively 6.18 mm. 6.23 mm, 6.68 mm, 7.20 mm and 8.18 mm.